2021
DOI: 10.3390/ani11041075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biscuit Flour and Fermented Defatted “Alperujo” Co-Administration on Intestinal Mucosa Morphology and Productive Performance in Laying Hens

Abstract: In this study, the effects of co-administration with biscuit flour and fermented defatted “alperujo” (FDA) on gut health were evaluated in a batch of laying hens (Hy-Line 2015) on a commercial farm. Animals were divided into two groups: control group and treatment group; and histological and morphometric analyses of all sections of the intestine (duodenum, jejunum, ileum, cecum and rectum) were performed at 10, 18, 25, 50 and 75 weeks of age. During the whole productive period, a decrease in the mortality rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This is in agreement with previous reports, which showed that dietary 25-OHD 3 improved the expression of intestinal barrier-related genes, thus improving intestinal integrity [ 40 ]. In one study with aged laying hens, combined treatment of biscuit meal and a by-product of modified olive oil maintained intestinal morphology, improved digestive function, and increased egg production, thus counteracting the adverse effects of age on intestine morphology [ 46 ]. Therefore, we deduce that compared with VD 3 , 25-OHD 3 may improve performance, egg quality, circulation of hormones, and mineral contents via an enhancement effect on intestinal morphology for better nutrient utilization.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous reports, which showed that dietary 25-OHD 3 improved the expression of intestinal barrier-related genes, thus improving intestinal integrity [ 40 ]. In one study with aged laying hens, combined treatment of biscuit meal and a by-product of modified olive oil maintained intestinal morphology, improved digestive function, and increased egg production, thus counteracting the adverse effects of age on intestine morphology [ 46 ]. Therefore, we deduce that compared with VD 3 , 25-OHD 3 may improve performance, egg quality, circulation of hormones, and mineral contents via an enhancement effect on intestinal morphology for better nutrient utilization.…”
Section: Discussionmentioning
confidence: 99%